2010
DOI: 10.1007/s10029-010-0706-8
|View full text |Cite
|
Sign up to set email alerts
|

Open tension-free Lichtenstein repair of inguinal hernia: use of fibrin glue versus sutures for mesh fixation

Abstract: Tissucol fibrin glue for mesh fixation in the Lichtenstein repair of inguinal hernia shows advantages over sutures, including lower incidence of complications such as pain, numbness, and discomfort, and should be considered as a first-line option for mesh fixation in hernioplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 14 publications
(12 reference statements)
3
47
0
Order By: Relevance
“…Several studies in various hernia repairs both open and laparoscopic using fibrin glue have shown promising results. 8,9 This is further authenticated by our study.…”
Section: Mechanism Of Actionsupporting
confidence: 68%
“…Several studies in various hernia repairs both open and laparoscopic using fibrin glue have shown promising results. 8,9 This is further authenticated by our study.…”
Section: Mechanism Of Actionsupporting
confidence: 68%
“…Mesh biomaterial in the form of lightweight mesh and heavyweight mesh has also been reported to be involved in the aetiology and pathogenesis of chronic groin pain [12][13][14][15]. Mesh fixation techniques potentially contributing to the development of chronic groin pain include the use of staples, tackers, sutures, autologous glues and synthetic glues [16][17][18][19][20][21]. Various measures to counteract the issues related to CGP and less predominantly related to hernia recurrence are being explored continuously.…”
Section: Introductionmentioning
confidence: 99%
“…The pain perceptions were significantly higher in the suture group as compared to the fibrin glue group (p value <0.001). The study by Negro et al [15] also showed that the mean pain score was significantly lower in the fibrin glue group than the suture group (2.5 vs. 3.2, p<0.001) and fibrin glue group patients also experienced less intense pain (0.6 vs. 1.2; p=0.001).…”
Section: Discussionmentioning
confidence: 86%